2020
DOI: 10.1088/1748-9326/ab9270
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution from wildfires and human health vulnerability in Alaskan communities under climate change

Abstract: Alaskan wildfires are becoming more frequent and severe, but very little is known regarding exposure to wildfire smoke, a risk factor for respiratory and cardiovascular illnesses. We estimated long-term, present-day and future exposure to wildfire-related fine particulate matter (PM 2.5 ) across Alaska for the general population and subpopulations to assess vulnerability using observed data for the present day (1997–2010), modelled estimates for the present day (1997–2001), and modelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 72 publications
0
9
0
1
Order By: Relevance
“…There is some evidence of increased risk of hospitalization for respiratory illness associated with WFS among African-Americans in the western U.S. , and among Indigenous people in Australia (Hanigan et al, 2008). A recent modeling study found that because of their geographic distribution in areas of high WFS concentration in Interior Alaska, African-Americans and Alaskan Athabascans may be more likely to be exposed (Woo et al, 2020). This is the first study to show an increased risk of adverse health outcomes associated with WFS among Alaska Native people.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of increased risk of hospitalization for respiratory illness associated with WFS among African-Americans in the western U.S. , and among Indigenous people in Australia (Hanigan et al, 2008). A recent modeling study found that because of their geographic distribution in areas of high WFS concentration in Interior Alaska, African-Americans and Alaskan Athabascans may be more likely to be exposed (Woo et al, 2020). This is the first study to show an increased risk of adverse health outcomes associated with WFS among Alaska Native people.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple social vulnerability indices include race or ethnicity based indicators for social vulnerability which have been found to be good predictors of susceptibility to heat (21,22,26,32,37,44,46,58,72,95,98,111,116,119,(158)(159)(160)(161)(162)(163)(164). This is attributed to the history of structural disadvantage and discrimination faced by minority communities (111,112).…”
Section: Race Ethnicity Minority and Immigrationmentioning
confidence: 99%
“…There are several indicators that measure socioeconomic status at individual and area levels, including household income (28,36,50,53,70,136,148,(166)(167)(168)(169)(170), neighborhood deprivation (105,137,144), labor force participation (42,48,148), poverty (22,24,48,58,62,70,72,73,81,85,89,90,93,95,98,100,102,111,112,116,162,(171)(172)(173), gross domestic product (174)(175)(176), income inequality (172,176,177), unemployment (41,49,…”
Section: Economics and Socioeconomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change has already begun to intensify wildfire activity in portions of the western United States and is anticipated to continue increasing activity in the coming years [4]. Alaska's forests are anticipated to burn more severely, be susceptible to more fire danger days, and smoke from wildfires is expected to pose an increased risk to Alaskans under potential future climate scenarios [5][6][7][8]. The Intergovernmental Panel on Climate Change (IPCC) identifies how climate change affects wildfire regimes including increased risk and severity [9].…”
Section: Introductionmentioning
confidence: 99%